Potential Formulation via Differential Forms

Potential Formulation via Differential Forms#

by Stéphane Haussler

Warning

This is a very first draft

In this page, I derive the potential formulation of the equations of Mr. Maxwell via differential form. This article in its current form is a first draft and may contain errors.

Inhomogenous Maxwell equations via differential forms

\[\begin{split}d\:⋆ \left[ \begin{aligned} - & \E^x \; dt ∧ dx \\ - & \E^y \; dt ∧ dy \\ - & \E^z \; dt ∧ dz \\ & B^x \; dy ∧ dz \\ & B^y \; dz ∧ dx \\ & B^z \; dx ∧ dy \\ \end{aligned} \right] = \begin{bmatrix} + μ_0 c ρ \; dx ∧ dy ∧ dz\\ - μ_0 J^x \; dt ∧ dy ∧ dz\\ - μ_0 J^y \; dt ∧ dz ∧ dx\\ - μ_0 J^z \; dt ∧ dx ∧ dy\\ \end{bmatrix}\end{split}\]

Homogenous Maxwell equations via differential forms

\[\begin{split}d \left[ \begin{aligned} - & \E^x \; dt ∧ dx \\ - & \E^y \; dt ∧ dy \\ - & \E^z \; dt ∧ dz \\ & B^x \; dy ∧ dz \\ & B^y \; dz ∧ dx \\ & B^z \; dx ∧ dy \\ \end{aligned} \right] = 0\end{split}\]
\[d F^{♭♭} = 0\]

Potential formulation

Taking the exterior derivative of any differential form \(A\) twice is zero

\[ddA = 0\]

Since \(dA = F^{♭♭}\), we can infer that \(A\) is a one-form \(A=A^{♭}\). From the Homogenous equations we obtain:

\[\begin{split}d\:d \left[ \begin{alignedat}{2} - & φ & dt \\ & A^x & dx \\ & A^y & dy \\ & A^z & dz \\ \end{alignedat} \right] = 0\end{split}\]

Now from the inhomogenous equations:

\[\begin{split}d\:⋆ d\left[ \begin{alignedat}{2} - & φ \; & dt \\ & A^x \; & dx \\ & A^y \; & dy \\ & A^z \; & dz \\ \end{alignedat} \right] = \begin{bmatrix} + μ_0 c ρ \; dx ∧ dy ∧ dz \\ - μ_0 J^x \; dt ∧ dy ∧ dz \\ - μ_0 J^y \; dt ∧ dz ∧ dx \\ - μ_0 J^z \; dt ∧ dx ∧ dy \\ \end{bmatrix}\end{split}\]

Maxwell Equations are in short form:

\[d ⋆ d A^♭ = J^{♭♭♭}\]

As expected, we can add a term do A of the form \(dα\) since this is guaranteed to be zero and \(α\) can be any form:

\[\begin{split}α = number + \left[ \begin{aligned} α^t \; dt \\ α^x \; dx \\ α^y \; dy \\ α^z \; dz \\ \end{aligned} \right] + \left[ \begin{aligned} α^? \; d? ∧ d? \\ α^? \; d? ∧ d? \\ α^? \; d? ∧ d? \\ α^? \; d? ∧ d? \\ \end{aligned} \right] + \left[ \begin{aligned} α^? \; dx ∧ dy ∧ dz \\ α^? \; dt ∧ dy ∧ dz \\ α^? \; dt ∧ dz ∧ dx \\ α^? \; dt ∧ dx ∧ dy \\ \end{aligned} \right]\end{split}\]